2012
DOI: 10.1007/s11764-012-0219-9
|View full text |Cite
|
Sign up to set email alerts
|

Unmet adolescent and young adult cancer survivors information and service needs: a population-based cancer registry study

Abstract: Purpose We described unmet information and service needs of adolescent and young adult (AYA) cancer survivors (15-39 years of age) and identified sociodemographic and health-related factors associated with these unmet needs. Methods We studied 523 AYAs recruited from 7 population-based cancer registries, diagnosed with acute lymphocytic leukemia, Hodgkin lymphoma, non-Hodgkin lymphoma, germ cell cancer or sarcoma in 2007-08. Participants completed surveys a median of 11 months from diagnosis. Multivariable l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
300
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 288 publications
(319 citation statements)
references
References 28 publications
17
300
0
2
Order By: Relevance
“…Further, the barriers and facilitators that were identified among AYA survivors are consistent with prior findings that AYA survivors have unmet informational needs, want assistance with healthy lifestyle behaviors, including via peer support, but could experience barriers to engaging in intervention programs. 10,28,46,47 The results have several implications for interventions aiming to support AYA survivors' adherence to exercise and physical activity recommendations. First, the findings on barriers and facilitators indicate that there is a variety of modifiable factors (e.g., motivation, mood, self-efficacy) that interventions could target.…”
Section: Discussionmentioning
confidence: 93%
“…Further, the barriers and facilitators that were identified among AYA survivors are consistent with prior findings that AYA survivors have unmet informational needs, want assistance with healthy lifestyle behaviors, including via peer support, but could experience barriers to engaging in intervention programs. 10,28,46,47 The results have several implications for interventions aiming to support AYA survivors' adherence to exercise and physical activity recommendations. First, the findings on barriers and facilitators indicate that there is a variety of modifiable factors (e.g., motivation, mood, self-efficacy) that interventions could target.…”
Section: Discussionmentioning
confidence: 93%
“…There are strong reasons to believe that this age group may be at particular risk for poor dental care as the recent AYA Hope Study detailed several healthcare gaps for survivors, of AYA cancer including report of unmet medical needs for more than 50% of the sample. 17 In general, these survivors report foregoing medical care due to cost barriers more often than individuals without a history of cancer. 4 Insurance coverage is a particularly important determinant of dental care access.…”
Section: Introductionmentioning
confidence: 99%
“…4 In psychosocial research, the majority of patient-reported outcome instruments have been validated either for children < 18 years of age or for adults 18 years of age or older; very few span both age groups, although research to address this deficit is ongoing. 19,20 As initial steps toward the goal of collecting prospective psychosocial data on AYAs, LIVESTRONG supported two initiatives: (1) NCI's Adolescent and Young Adult Health Outcomes and Patient Experience (AYA HOPE) study, a population-based analysis that determined best practices for medical record collection, validated the feasibility of assessing psychosocial outcomes in recent survivors of AYA cancer, [21][22][23] and reported on the social information and service needs, health-related quality of life, work disparities, and educational disparities of AYAs with cancer [24][25][26] and (2) the Alliance's AYA cohort study, a prospective, multi-institutional study testing the feasibility of collecting AYAs' clinical, psychosocial, and health-related qualify of life data at several time points during the first year of cancer therapy. 4 The Alliance made strides toward coordinating the research and clinical efforts of the pediatric and adult branches of NCI-designated cancer centers through the formation and coordination of the Cancer Centers Working Group (CCWG).…”
Section: Research and Tool Developmentmentioning
confidence: 99%